The effect of drinking yogurt on the microhardness of posterior composites resin (Mustansiria Dental Journal, 2018)
Background :This study was conducted to evaluate the effect of yogurt on thesurface microhardness of two types of composite resins; (Filtek™ P90 Low ShrinkPosterior Restorative, 3M ESPE,USA), and (Filtek™ Z350 Posterior Restorative, 3MESPE,USA).Forty samples of composite were prepared by using cylindrical mold (2mm inhight and 8mm in diameter )..All specimens were stored in plastic container thatcontain distilled water and incubated 37cº for 24 hours before they were tested. twentysamples of each type of composite were divided into two groups (10) for each ,baseline measurements for surface microhardness test was taken for all compositesamples using the micromet microhardness tester (Vichers hardness tester) with al00g load was applied for 15 seconds in which three indentations were made for eachsample and converted into Vickers Hardness Number (VHN ) .After baselinemeasurement 10 samples of each type of composite were alternately immersedmanually by holding the specimen by a pair of tweezers from its sides, , in drinkingyogurt (Activia ,KSA) and artificial saliva for 10 cycles 5 seconds each at roomtemperature (25cº). This was repeated three times a day (8am,4pm,12am) at 8hoursintervals for one week. the other 10 samples for each type of composite wereimmersed in artificial saliva only. The total soaking time in both drinking yogurt andsaliva was 100 seconds. After the soaking sequence was completed the specimen wasrinsed with distilled water and subjected to surface microhardness test (Vichershardness tester).Descriptive statistics(mean values and standard deviations with the minimum andmaximum values and Statistical analysis of data by using student t - test for all groupswas carried out between the means of each type of composites ,the results showed asignificant reduction in VHN values (at P